HGG-22. PHASE 1b STUDY POLIO VACCINE SABIN-RHINOVIRUS POLIOVIRUS (PVSRIPO) FOR RECURRENT MALIGNANT GLIOMA IN CHILDREN. Issue 2 (22nd June 2018) - Ashley, David M; Thompson, Eric M; Landi, Daniel; Desjardins, Annick; Friedman, Allan H; Threatt, Stevie; Herndon, II, James E; Boulton, Susan; McSherry, Frances; Lipp, Eric S; Sampson, John H; Friedman, Henry S; et al.
Abstract: BACKGROUND: Prognosis of recurrent World Health Organization (WHO) grade IV malignant glioma (GBM) in children is dismal with no effective therapy. We have recently performed a dose-finding and toxicity study within adults with GBM, evaluating the recombinant non-pathogenic polio/rhinovirus chimera (PVSRIPO) by intratumoral convection-enhanced delivery (CED). PVSRIPO recognizes the poliovirus receptor CD155, which is widely expressed in neoplastic cells of solid tumors and in major components of tumor stroma. We have commenced a Phase Ib study to evaluate feasibility, safety, and preliminary evidence of efficacy of the optimal adult dose in a pediatric population. METHODS: Patients with a recurrent supratentorial WHO Grade III malignant glioma (anaplastic astrocytoma, anaplastic oligoastrocytoma, anaplastic oligodendroglioma, anaplastic pleomorphic xanthoastrocytoma, ependymoma) or WHO Grade IV malignant glioma (glioblastoma, gliosarcoma) based on imaging studies with measurable disease (≥ 1 cm and ≤ 5.5 cm of contrast-enhancing tumor) will be enrolled. A stereotactic biopsy will be performed prior to virus administration. Immediately following the stereotactically-guided tumor biopsy, a catheter will be implanted in the operating room. PVSRIPO will then be delivered intratumorally by CED, using the catheter placed within the enhancing portion of the tumor, at a dose of 5 x 10 7 TCID over 6.5 hours. CONCLUSION: We will confirm the activity of intratumoral PVSRIPO infusion in recurrent WHO grade III or IV malignant glioma in the absence of neurovirulent potential in children.